Why Good Quality Care Needs Philosophy More Than Compassion; Comment on "Why and How Is Compassion Necessary to Provide Good Quality Healthcare?" - Carlo Leget (Kerman University of Medical Sciences, 2015)
Although Marianna Fotaki's Editorial is helpful and challenging by looking at both the professional and institutional requirements for reinstalling compassion in order to aim for good quality healthcare, the causes that hinder this development remain unexamined. In this commentary, 3 causes are discussed; the boundary between the moral and the political; Neoliberalism; and the underdevelopment of reflection on the nature of care. A plea is made for more philosophical reflection on the nature of care and its implications in healthcare education.